Analisis Mekanisme Penyelesaian Pembiayaan Bermasalah Griya IB Hasanah Pada Bni Syariah Kantor Cabang Jakarta Barat - Delia Paramitha; Ahmad Munawaruzaman (Jurusan Manajemen Dakwah, Fakultas Ilmu Dakwah dan Ilmu Komunikasi, UIN Syarif Hidayatulla, 2019)
providing financing for Islamic banks, they are vulnerable to experience nonperforming loans. These problematic financing must be immediately addressed and resolved,so that the bank does not experience losses. BNI Syariah as a financial institution which distributes financing to customers must also experience the financing problem which is due to internal and external factors. This research focuses on themechanism of financing problem settlement on Griya iB Hasanah products which are BNI Syariah's superior products The objective of this study was to determine the factors causing the occurrence of problematic financing on iBhasanahgriya products and any settlement mechanism conducted by BNI Syariah West Jakarta branch office. This research uses a qualitative methodology with descriptive techniques. The data obtained from the institution is then processed systematically in the form of written words, archives and oral, as well as the observed behavior to obtain an overview of information related to the title of the study. It can be concluded that the results of this study are the mechanism of financing problem solving on Griya iB Hasanah products conducted by BNI Syariah is quite good, namely by conducting coaching with customers, restructuring, and completing with the auction paths of course with directed goals,andit continues to improve every year.